Testing a mindset intervention as a resilience factor among Latino/a students in science. Issue 1 (2nd January 2020) - Schmidt, Jennifer A.; Shumow, Lee
ABSTRACT: Latinos/as experience underachievement and underrepresentation in science. Mindset beliefs contribute to positive academic outcomes among students generally, but are understudied among Latinos/as in science. In this quasi-experimental study, Latino/a students expressed initial mindset-related beliefs shown to be less generative of success in science than their non-Latino/a classmates. A six-week mindset intervention positively influenced Latinos/as' mindset beliefs and self-perceptions compared to a control group. Gains were generally similar in magnitude for Latino/a and non-Latino/a students, suggesting that mindset may be compensatory rather than protective among Latino/a youth. Gender differences in initial mindset beliefs and response to the intervention are discussed.